Umpolung Synthesis of Diarylmethylamines via Palladium‐ Catalyzed Arylation of N‐Benzyl Aldimines. Issue 12 (12th May 2016) - Li, Minyan; Yucel, Baris; Jiménez, Jacqueline; Rotella, Madeline; Fu, Yue; Walsh, Patrick J.
Abstract: An umpolung synthesis of diarylmethylamine derivatives is presented. This reaction entails a palladium‐catalyzed arylation of 1, 3‐diaryl‐2‐azaallyl anions, in situ generated from N ‐benzyl aldimines. A Pd(NIXANTPHOS)‐based catalyst together with hindered silylamide bases enabled the coupling of aldimines with aryl bromides in good to excellent yields without product isomerization. Moreover, regioselectivity in the arylation of unsymmetrical 1, 3‐diaryl‐2‐azaallyl anions was studied. This method is suitable for a gram scale synthesis of diarylmethylamine derivatives at room temperature without use of a glove box. Abstract :